ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI PENGHASILAN ANGKUTAN UMUM (STUDI KASUS PETE-PETE DI KAB. GOWA) - Rusdi, H Muh; Rukianti, Rukianti (Jurnal Ekonomi Balance, 2017)
This study aims to determine the factors that affect the income of public transportation pete-pete case study in gowa district. The type of data used in this study, ie data concerning factors that affect the income of public transport obtained from DISHUB gowa district as well as related agencies and data sources used are secondary data. The model used to analyze the relationship between the two variables, that is using multiple linear regression analysis. The result of the research shows that the transportation tariff has significant effect to the transportation revenue, the significant number of population to the transportation income, and the transportation line has significant effect to the income of the regional transportation revenue Gowa.